Epidermal Cells Methods and Protocols - Turksen, Kursad; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
In recent years our ability to understand and manipulate epidermal cells has increased tremendously, opening significant new possibilities in both basic science research and in regenerative medicine, including wound healing and transplantation. In Epidermal Cells: Methods and Protocols, a panel of experienced basic and clinical researchers describe in step-by-step detail the powerful methods they have developed and optimized to analyze and manipulate epidermal cell precursors and mature epidermal cells. These protocols cover different methods and models for culturing epidermal cells, for enriching very early epidermal progenitors, as well as for studying epidermal cell commitment and differentiation both in vitro and in vivo. Topics of special interest include the derivation, characterization, and utility of epidermal stem cells, mature epidermal cells and their characterization, and applications in regenerative medicine. The protocols follow the successful Methods in Molecular Biology series format, each one offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. State-of-the-art and highly practical, Epidermal Cells: Methods and Protocols offers experienced and novice investigators alike an invaluable collection of readily reproducible techniques designed to broaden not only our understanding of the biology of epidermal cells, but also their utility in normal tissue homeostasis and regenerative medicine applications.
Keratinocyte and Organ Cultures -- Primary Mouse Keratinocyte Culture -- Serial Cultivation of Primary Adult Murine Keratinocytes -- Keratinocyte Culture in the Absence of Substrate Attachment -- Application of Genetically Modified Feeder Cells for Culture of Keratinocytes -- Organ Culture of Developing Mouse Skin and Its Application for Molecular Mechanistic Studies of Morphogenesis -- Experimental Models to Analyze Differentiation Functions of Cultured Keratinocytes In Vitro and In Vivo -- In Vitro Fabrication of Engineered Human Skin -- Epidermal Stem Cells -- In Vivo Labeling and Analysis of Epidermal Stem Cells -- Method for the Harvest and Assay of In Vitro Clonogenic Keratinocytes Stem Cells From Mice -- FACS Enrichment of Human Keratinocyte Stem Cells -- Isolation, Characterization, and Culture of Epithelial Stem Cells -- Keratin 19 as a Stem Cell Marker In Vivo and In Vitro -- Analysis of Epidermal Differentiation -- Immunolocalization in the Epidermis -- Epidermal Cell Analysis by RT-PCR -- Whole-Mount Assays for Gene Induction and Barrier Formation in the Developing Epidermis -- Analysis of Early Epidermal Development in Zebrafish -- Analysis of E2F Factors During Epidermal Differentiation -- Analysis of HOX Homeodomain Proteins and Gene Transcripts in the Epidermis -- Apoptosis in the Epidermis -- Fate of Desmosomal Proteins in Apoptotic Epidermal Cells -- Analysis of Connexin 43 Expression on Keratinocytes Using Flow Cytometry -- MMP-9 and TIMP-1 Assays in Keratinocyte Cultures -- Characterization of Epithelial Cells in the Hair Follicle With S100 Proteins -- Immunoelectron Microscopic Analysis of Cornified Cell Envelopes and Antigen Retrieval -- Methods and Approaches for the Analysis for Epidermal Function -- Cell Kinetic Analysis in Artificial Skin Using Immunochemical Methods -- Proliferation, Differentiation, and Inflammation in Normal and Hyperproliferative Skin Using Multiparameter Flow Cytometry -- Fluorimetric DNA Assay of Cell Number -- Keratinocyte Transient Transfections -- Tetracycline-Regulated Gene Expression in Epidermal Keratinocytes -- Gene Targeting by Oligonucleotides in Keratinocytes -- Promoter Analysis in the Human SPRR Gene Family -- Stable Integration of Large PAC Constructs in Keratinocytes -- Targeted Somatic Mutagenesis in the Mouse Epidermis -- Methods to Study Protein-Protein Interactions -- Isolation of Recombinant Phage-Displayed Antibodies Recognizing Skin Keratinocytes -- Analysis of Tissue-Specific DNA Methylation During Development -- Serial Analysis of Gene Expression in Human Keratinocytes and Epidermis -- Methods for Gene Expression Profiling in Dermatology Research Using DermArray® Nylon Filter DNA Microarrays -- Two-Photon Fluorescence Imaging and Reactive Oxygen Species Detection Within the Epidermis -- Transplantation and Gene Therapy -- In Vivo Transplantation of Engineered Human Skin -- Epidermis-Targeted Gene Transfer Using In Vivo Electroporation -- Gene and Stem Cell Therapy of the Hair Follicle.
Keywords: Medicine; Internal medicine; Cell biology; Medicine & Public Health; Internal Medicine; Cell Biology; Electronic books